Pengaruh Motivasi dan Disiplin Kerja terhadap Prestasi Kerja Pegawai Negeri Sipil pada Kelurahan di Kecamatan Tamansari Kota Tasikmalaya - Nuri Masruroh; Rita Tri Yusnita; Arga Sutrisna (CV. Ulil Albab Corp, 2022)
This research is conducted by the objective to know the effects of motivation and work discipline on the work of performance government employees on the Village in Tamansari District Tasikmalaya City. The method used in this study is a quantitative approach with the causality method. Data collection techniues were obtained directly questionnaires distributed to 45 respondents who were government employees on the Village in Tamansari District Tasikmalaya City. the data analysis tool used in this study is path analysis. Based on the results of the study it can be seen that: (1)There is an influence of motivation on work discipline government employees on the Village in Tamansari District Tasikmalaya City positively and significantly. (2) There is an influence of motivation on the work performance government employees on the Village in Tamansari District Tasikmalaya City positively and significantly. (3) There is an influence of discipline on the work performance government employees on the Village in Tamansari District Tasikmalaya City positively but not significantly (4) There is an influence of motivation on work discipline on the work of perfomance government employees on the Village in Tamansari District Tasikmalaya City positively and significantly. (5) There is no influence and it is not significant motivation towards work performance through work discipline government employees on the Village in Tamansari District Tasikmalaya City.